Dosimetric properties of Li2B4O7:Cu, Ag, P solid detector. (August 2020) - González, P.R.; Ávila, O.; Escobar-Alarcón, L.; Mendoza-Anaya, D.
Abstract: This work presents results obtained following the preparation of lithium borate by the chemical reaction between lithium carbonate (Li2 CO3 ) and boric acid (H3 BO3 ), doping the host salt of lithium borate (Li2 B4 O7 ) with ions of copper, silver and phosphorus. With the obtained material dosimeters were produced in sintered pellet form which were exposed by gamma radiation that emitted from 60 Co source. The highest sensitivity was found for the sample of Li2 B4 O7 :Cu, Ag, P (in pellet form) with 0.45, 0.45 and 12 mol% of Cu, Ag and P, respectively, subjected to a thermal treatment at 1123 K during 2 h. The TL response shows linearity in the dose range from 0.005 to 100 Gy. The lower detection limit (LDL) was equal to 6.10 μGy. The fading was found to be 3% in the first ten days and 9% at the end of thirty days. The repeatability of TL measurements for twenty cycles, showed a variability coefficient equal to 4.15%. The glow curve shape of Li2 B4 O7 :Cu, Ag, P sintered pellet shows two peaks with general-kinetics order. This new material could be appropriate for dosimetry in clinical radiation applications. Highlights: Lithium borate was obtained by the solution-assisted method. This study report the dosimetric properties of Li2 B4 O7 :Cu, Ag, P solid detector. Effect of thermal treatment on the TL response was studied. Kinetics parameters were analyzed by deconvolution method.